Advances concerning multiscale methods and uncertainty quantification in EXA-DUNE - Bastian, Peter; Ippisch, Olaf; Müthing, Steffen (Software for Exascale Computing - SPPEXA 2013-2015, 2016)
In this contribution we present advances concerning efficient parallel multiscale methods and uncertainty quantification that have been obtained in the frame of the DFG priority program 1648 Software for Exascale Computing (SPPEXA) within the funded project Exa-Dune. This project aims at the development of flexible but nevertheless hardware-specific software components and scalable high-level algorithms for the solution of partial differential equations based on the DUNE platform.